Musical Compositions Based On A Study Of The Figurative And Textural Dialectic In Selected Art Works: Music As Metaphorical Reflections - Ngiao@Yeow , Tzu-En (2010)

(untitled)
Correspondences between the visual arts and the musical arts have inspired many composers to write music based on themes and subjects in specific visual art works. Many musical compositions have also been graphically conceptualised in regard to their distribution of and relationships between musical parameters as well as their formal and structural construction in time. This thesis aims to formulate a set of compositional methods that attempt to derive and translate into musical materials from the visual arts via an analogy of the relationships between graphical elements in selected visual art works.